Excess subcutaneous tissue may preclude intramuscular delivery when using adrenaline autoinjectors in patients with anaphylaxis. Issue 6 (29th March 2015) - Johnstone, J.; Hobbins, S.; Parekh, D.; O'Hickey, S.
Abstract: Intramuscular adrenaline is the gold standard treatment for anaphylaxis. Intramuscular injection provides more rapid and higher plasma concentrations than subcutaneous routes. Given the increasing epidemic of obesity patients are at increased risk of subcutaneous delivery, we therefore assessed the depth of subcutaneous tissue in a population of patients with anaphylaxis. Patients already prescribed adrenaline autoinjectors (AAIs) for anaphylaxis were examined with ultrasound, and measurements of skin‐to‐muscle depth (STMD) at anterolateral thigh and anterior thigh were performed. Twenty‐eight patients (23 female, 5 male) with an age range of 18–75 took part in the study, and in 68%, the STMD was greater than AAI needle length (15.02 mm), using the anterolateral thigh as the recommended administration site. The key predictors for increased STMD were female gender (P=0.0003) and a BMI > 30 (P=0.04). AAIs require longer needles to ensure intramuscular administration, and ultrasound at point of prescription would aid needle length selection.